Effects of a Pharmacy-Driven Perisplenectomy Vaccination Program on Vaccination Rates and Adherence to Guidelines - Meier-Stephenson, Vanessa (Canadian Society of Hospital Pharmacists, 2014)
BACKGROUND: Overwhelming postsplenectomy infection is a serious potential outcome for patients who have undergone resection of the spleen and is associated with a high mortality rate. The most common bacterial causes are the encapsulated organisms Streptococcus pneumoniae, Neisseria meningitidis, and Hemophilus influenzae type B, all of which are vaccine-preventable. Current guidelines recommend vaccination against these 3 bacteria, but adherence to these guidelines is less than ideal. In 2007, a “perisplenectomy vaccination kit” was introduced at the authors’ institution to improve compliance with immunization guidelines by making the vaccines and necessary information for patients and providers more readily available. OBJECTIVE: To evaluate and compare vaccination rates for patients who underwent splenectomy before and after introduction of the perisplenectomy vaccination kit and, secondarily, to identify any characteristics unique to those who did not receive appropriate perisplenectomy vaccinations. METHODS: In this observational study, performed at the QEII Health Sciences Centre of Capital Health in Halifax, Nova Scotia, data were reviewed for patients who underwent splenectomy between 2008 and 2011. Vaccination rates and other descriptive statistics were calculated and compared with data for a 3-year period before implementation of the program. RESULTS: Vaccination rates in the 3-year period following implementation of the perisplenectomy vaccination kit were 100% against S. pneumoniae, 97% against N. meningitidis, and 93% against H. influenzae type B. The corresponding rates in the 3 years before introduction of the kit were 91%, 75%, and 68%, respectively. No characteristics predicting inadequate immunization were identified in univariate or multivariate analysis. CONCLUSION: Introduction of a pharmacy-driven perisplenectomy vaccination kit program improved rates of appropriate vaccination for patients who underwent splenectomy.